Informática jurídica: un ejemplo de su aplicación práctica: la tecnificación de servicio registral en la república oriental del Uruguay : Situación actual: procesos en implementación - Martínez Puglia, Lucía (2013)
The present work is to prove the actual validity of legal information in a particular case: its practical application in the Public Records at the Oriental Republic of Uruguay. It mentions the objective of registration activity as part of preventive legal security, how it has developed the process of computerization in order to meet this objective through communication technologies and information in the various areas covered by the Public Records and how that process is being developed at present, achieving through legal information registry, get safer processes and agile, with great benefits for users. It also exposes the current stage that projects and is working on incorporating advanced electronic signature of the Registrar to issue registration information to then apply this new technology to the registration of documents in the records. At work, we conclude with what we understand is demonstrated finally: the practical and contemporary relevance of Legal Informatics, which has yet to conclude ongoing developments. The case relates primarily from the author's experience as a member and Director of the Law area of the Center for computations of the Direction General of Records of the Uruguay.